2019
DOI: 10.1128/jvi.00978-19
|View full text |Cite
|
Sign up to set email alerts
|

Avian Flavivirus Infection of Monocytes/Macrophages by Extensive Subversion of Host Antiviral Innate Immune Responses

Abstract: Avian Tembusu virus (TMUV) is a newly emerging avian pathogenic flavivirus in China and Southeast Asia with features of rapid spread, an expanding host range, and cross-species transmission. The mechanisms of its infection and pathogenesis remain largely unclear. Here, we investigated the tropism of this arbovirus in peripheral blood mononuclear cells of specific-pathogen-free (SPF) ducks and SPF chickens and identified monocytes/macrophages as the key targets of TMUV infection. In vivo studies in SPF ducks an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 61 publications
3
23
1
Order By: Relevance
“…In the study by Chvala et al (2004), USUV was detected in macrophages and dendritic cells of naturally infected blackbirds [18]. Together, these results demonstrate that USUV may target the immune cells in birds, which could play an important role in the spread of the virus in a wide variety of tissues, as described for WNV [59] and Tembusu virus [60] (a mosquito-borne flavivirus pathogenic for certain waterfowl birds).…”
Section: Discussionmentioning
confidence: 62%
“…In the study by Chvala et al (2004), USUV was detected in macrophages and dendritic cells of naturally infected blackbirds [18]. Together, these results demonstrate that USUV may target the immune cells in birds, which could play an important role in the spread of the virus in a wide variety of tissues, as described for WNV [59] and Tembusu virus [60] (a mosquito-borne flavivirus pathogenic for certain waterfowl birds).…”
Section: Discussionmentioning
confidence: 62%
“…In addition to metabolism, the signal pathway categories of immune system were enriched in, such as RIG-I-like receptor signaling pathway. The genome-wide transcriptome analyses of DTMUV-infected macrophages revealed that the inductions of alpha interferon and beta interferon were blocked on transcription and translation levels in response to viral infection, despite the activation of major pattern recognition receptor signaling (54). Deep study showed that DTMUV non-structural protein 1 interacts with the adaptor protein mitochondrial antiviral signaling to inhibit the mitochondrial antiviral signaling pathway, resulting in the impaired induction of beta interferon (55).…”
Section: Discussionmentioning
confidence: 99%
“…RNA was isolated from cells using EasyPure RNA Purification Kit (TransGen Biotech, Beijing, China) according to the manufacturer's protocol. RT-qPCR and absolute RT-qPCR were performed using the SYBR PrimeScriptTM Kit (TaKaRa Bio Inc, Tokyo, Japan) as described previously [29]. The standers of the absolute RT-qPCR were prepared by cloning the PCR products of ICP4, ICP27, UL48, gI, gG, and gC genes of ILTV into the pMD18-T plasmid (TaKaRa-Bio, Shiga, Japan) according to the manufacturer's instructions.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%